Formalin Analysis in Anchovies (Stolephorus sp) at Simpang Limun Market, Medan City - Dinda Sari Utami; Melati Yulia Kusumastuti; Syarifah Nadia; Anny Sartika Daulay; Ziza Putri Aisyia Fauzi; Helni Maulida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Salted anchovies (Stolephorus sp.) are a long-known and popular delicacy among Indonesians. Salting is the most common method of preserving fish. Table salt (NaCl) is the most common and widely used method. The salting process takes a long time, leading traders who want to make large profits to add formalin to the fish to prevent it from rotting quickly and to preserve it for a long time. This study aims to determine whether anchovies sold at the Simpang Limun market in Medan City contain formalin and the levels of formalin identified in salted anchovies using the VIS spectrophotometry method. The research was carried out employing a purposive approach, and the samples analyzed were anchovies sourced from both the Simpang Limun market and the Modern Market. The independent variables in this research included anchovies, Schryver reagent, KMnO4 reagent, Schiff reagent, as well as VIS Spectrophotometry. To perform qualitative analysis of formalin, KMnO4 reagent, Schryver reagent, and Schiff reagent were utilized, while the quantitative analysis was conducted using the VIS spectrophotometry method with Schiff reagent. The findings from the validation of the method indicated a detection threshold of 10.39 µg/mL and a quantitative limit of 34.65 µg/mL, with formalin recovery rates in anchovy samples between 98.8 and 101.16%. Qualitative examinations of six anchovy samples returned negative outcomes, and the quantitative analysis across all samples supported the findings, revealing that only one sample was free of formalin.